Pay Later E-Commerce Development Phenomenon Review From Sharia Economic Point - Nurwahidah Firdaus; Eko Suyono; Dewi Susilowati3 Susilowati; Wahyudin Wahyudin (Agregat: Jurnal Ekonomi dan Bisnis, 2022)
Pay later is a financial technology (fintech) innovation that has the concept of buying now and paying later. The problem highlighted in Islam is that pay later leads to a consumptive lifestyle to be a spendthrift which is not recommended according to the Shari'a laws. The purpose of this study is to find out and dig deeper into the use of the right contract in e-commerce pay later transactions as well as to find out and dig deeper into Sharia-compliant etiquette in e-commerce pay later transactions.  This paper is a causal relationship study that is using a qualitative approach. Data are collected through an archival study based on the literature.  Based on the analysis this study concludes that online credit buying and selling contracts which are suitable with Islamic laws are Qardh and Murabahah contracts as the right and appropriate contracts to be applied in Pay later transactions. It is because Qardh and Murabahah are in accordance with the fatwa of Majelis Ulama Indonesia where the contracts explain how the delay in payment or debit transactions are carried out.